ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALMAN Z-SCORE PADA PT MATAHARI DEPARTMEN STORE, Tbk - MUNIARTY, PUJI; M Rimawan; Ovriyadin; Tri Wahyuni Alifah; M Syukur Dwiriansyah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The spread of retail companies in each region will incur quite high costs followed by the emergence of similar business competitors, both companies that have not yet and have already listed on the Indonesian Stock Exchange. Opening a retail subsidiary will incur high operational costs. So it will have an impact on company expenses. With Covid-19, many retail companies have seen their income levels decline and are even on the verge of bankruptcy. One of the causes of bankruptcy is the COVID-19 pandemic that has hit the whole world, causing a decrease in buyer interest, thus affecting company revenues and profits. Bankruptcy is a condition where a company shows an inability to operate properly because the financial difficulties it is experiencing are very severe. This research aims to determine the prediction of bankruptcy at PT Matahari Department Store Tbk using the Altman Z-Score method. This type of research is descriptive research with a quantitative approach. The research data source used is secondary data with data analysis techniques, namely hypothesis testing (one sample t-test). Based on the results of the hypothesis test, it shows that the bankruptcy assessment of PT Matahari Department Store Tbk using the Altman Z-Score method has no potential for bankruptcy.